2008
DOI: 10.1074/jbc.m707965200
|View full text |Cite
|
Sign up to set email alerts
|

CPT1c Is Localized in Endoplasmic Reticulum of Neurons and Has Carnitine Palmitoyltransferase Activity

Abstract: CPT1c is a carnitine palmitoyltransferase 1 (CPT1) isoform that is expressed only in the brain. The enzyme has recently been localized in neuron mitochondria. Although it has high sequence identity with the other two CPT1 isoenzymes (a and b), no CPT activity has been detected to date. Our results indicate that CPT1c is expressed in neurons but not in astrocytes of mouse brain sections. Overexpression of CPT1c fused to the green fluorescent protein in cultured cells demonstrates that CPT1c is localized in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
185
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 153 publications
(197 citation statements)
references
References 25 publications
11
185
1
Order By: Relevance
“…In agreement with the literature (16), we found that CPT-1a and -1c were the most abundant CPT-1 isoforms expressed in brain cells. However, the expression of CPT-1c in cultured astrocytes is not consistent with earlier studies showing a neuronal localization in the adult mouse brain (44,45). This discrepancy could be related to the age of the animals used to generate astrocytes (P1) and/or the culture conditions.…”
Section: Discussioncontrasting
confidence: 48%
“…In agreement with the literature (16), we found that CPT-1a and -1c were the most abundant CPT-1 isoforms expressed in brain cells. However, the expression of CPT-1c in cultured astrocytes is not consistent with earlier studies showing a neuronal localization in the adult mouse brain (44,45). This discrepancy could be related to the age of the animals used to generate astrocytes (P1) and/or the culture conditions.…”
Section: Discussioncontrasting
confidence: 48%
“…is located in the mitochondrial membrane and CPT1C is expressed in the endoplasmic reticulum of neurons where although it has CPT1 activity, it does not participate in mitochondrial fatty-acid oxidation [12]. Interestingly, our group has generated a mutant form of CPT1A insensitive to malonyl-CoA (CPT1A M593S), and a mutant form of carnitine acetyltransferase (CrAT) that swaps its preference from short to LCFA-CoA (CrAT D356A/M564G).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, for example, the H483A mutant of rat CPT1A shows a 50% decrease in the affinity for malonyl-CoA (18) and the A478D mutation affected the affinity for palmitoyl-CoA (18). Interestingly, Ala 478 is not conserved in the most recently described mammalian isoform, CPT I-C, which has a very low catalytic constant when carnitine and long chain acyl-CoA are used as substrates (14,24). In all of the insect CPT1 genes studied, the residues equivalent to His 483 and Ala 478 in rat CPT1A are both encoded within the alternatively spliced exons (6A/6B) and, importantly, are conserved in both variants generated from each of the insect CPT1 genes analyzed (Fig.…”
Section: Tablementioning
confidence: 99%